Capturing the Nature of Teacher and Learner Agency Demonstrating Creativity: Ethical Issues and Resolutions - Debra McGregor; Sarah Frodsham (MDPI AG, 2022)
This article will focus on the ethical dilemmas and concerns related to eliciting the nature of agency in classrooms that emerges in learning contexts. Agency is a somewhat elusive phenomena to evidence because it involves capturing signs and indications of thinking involved in negotiating meanings, the capacity for initiating, and constructional decision-making. These processes are often made explicit through dialogic and actional exchanges between teachers and/or learners. This includes taking account of activities engaged in, either independently or collaboratively. It also requires evidence of earlier happenings or interactions between classroom participants that might influence and shape later events. There is also concern about the ways that teachers' and learners' demonstrable originality or creativity are recognised and communicated for scrutiny by others. Additionally, ethical approval procedures (BERA 2018) require that research protects participants' anonymity, confidentiality, and dignity; therefore, research has to be carried out with integrity. Ensuring benefits from research are maximised and that no-one is harmed or made to feel uncomfortable requires the utmost care and balance between eliciting insightful data while maintaining the appropriate duty of care for participants. To achieve these objectives, multiple research methods were used. Audio and video recordings were transcribed and analysed to make sense of teacher and learner agency. The findings include an events map, photographic images, and dialogic episodes illustrating the nature of contrasting teacher and learner agency. The conclusion considers tensions that emerge as researchers seeking to characterize agency without compromising privacy.